Changes in life experiences of adults with intellectual disabilities in the COVID-19 pandemics in South Korea. Issue 4 (October 2021) - Kim, Min Ah; Yi, Jaehee; Sung, Jimin; Hwang, Shinyeong; Howey, Whitney; Jung, Sang Mi
Abstract: Background: The COVID-19 pandemic has had a significant impact on adults with intellectual disabilities who are dependent on community services. Objective: This study explored the experiences of adults with intellectual disabilities from their perspective during the COVID-19 pandemic in South Korea, where most community-based services were suspended. Methods: We conducted in-depth interviews with 15 adults with intellectual disabilities who lost access to services during COVID-19 pandemic. Inductive thematic analysis was conducted. Results: Five overarching themes emerged: changes in (a) daily life, (b) health behaviors, (c) family relationships, (d) social relationships, and (e) social participation. Most participants experienced the loss of daily routines and healthy behaviors, family conflicts, and social isolation, but they also developed new ways of adapting and finding a new normal. Conclusions: The findings offer valuable evidence of ways to develop and stabilize community-based services during a pandemic, with insights into the experiences of people with intellectual disabilities.